2009
DOI: 10.1590/s0101-98802009000300004
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da expressão tecidual do gene de reparo MLH1 e dos níveis de dano oxidativo ao DNA em doentes com câncer colorretal

Abstract: O dano oxidativo ao DNA provocado por radicais livres de oxigênio representa um dos principais mecanismos responsáveis pelas etapas iniciais da carcinogênese colorretal. O estresse oxidativo ocasiona erros de pareamento de bases possibilitando o aparecimento de mutações em genes controladores do ciclo celular. As células possuem um sistema de defesa representado pelos genes de reparo do DNA que corrigindo os erros de pareamento impedem o desenvolvimento de mutações. Poucos estudos avaliaram a relação entre dan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
(89 reference statements)
0
3
0
Order By: Relevance
“…Genetic studies have shown development of sporadic CRC is an evolutionary process that involves a series of sequential mutations or modifications in the expression of genes related to cell cycle 21 . It is already well established that the development of the CRC from the normal mucosa, is mediated by a sequence of mutations of genes controllers of cell cycle (the proliferation, differentiation, apoptosis and DNA repair) 8 , 30 .…”
Section: Introductionmentioning
confidence: 99%
“…Genetic studies have shown development of sporadic CRC is an evolutionary process that involves a series of sequential mutations or modifications in the expression of genes related to cell cycle 21 . It is already well established that the development of the CRC from the normal mucosa, is mediated by a sequence of mutations of genes controllers of cell cycle (the proliferation, differentiation, apoptosis and DNA repair) 8 , 30 .…”
Section: Introductionmentioning
confidence: 99%
“…Another one suggests that the methylation process can occur simultaneously in different repair systems 3,14,15 . In a previous study, evaluating the same group of patients, we found that the hMLH1 tgene had lower expression in tumor tissue when compared to normal tissue 29 . It is possible that the hMLH1 gene, one of the main components of the MMR DNA repair system, was also less expressed due to hypermethylation of its promoter region.…”
Section: Discussion Discussion Discussion Discussionmentioning
confidence: 73%
“…25 It was also found that MLH1 repair gene expression is higher in normal tissue than in cancer tissue, which demonstrated the importance of this gene in maintaining DNA integrity. 24,26 CONCLUSION TS, COX2, EGFR, MSH6, MLH1 and p53 expression, as measured through immunohistochemical analysis, was not associated with the clinical-pathological factors of the patients with colorectal adenocarcinoma studied, except for MLH1 in some cases. This marker showed a significant difference in expression between patients at stages III and IV and those at stages I to IV of colorectal adenocarcinoma.…”
Section: Discussionmentioning
confidence: 83%